Things on the Move - Bowers, Will (Romanticism on the Net)

(untitled) (Université de Montréal, 2023)
Moving, and the things people brought with them on the move, can take us many ways into, across, and out of Romantic Europe. This essay begins by reflecting on objects which represent the mass forced movements at the centre of Romanticism: the waves of immigration and exile spurred by the French Revolution and the unwilling transit of millions of Africans to enslavement in the Caribbean. I then turn to a more individualised account of what a European on the move might have taken with them, an approach which allows us to reflect both on the importance of the oft-ignored things that travellers moved with and on continuities between the Romantic attitudes and the modern material culture of travel. The objects described prompt an exploration of such broad topics as aesthetics, economics, reading practices, and the growing professionalisation of authorship, while also allowing for reflection on the personal and often emotional attachments that travellers had with their belongings.